ETIKA DRIYARKARA DAN RELEVANSINYA DI ERA POSTMODERN - Banin Diar Sukmono (Jurnal Filsafat "WISDOM", 2013)
Driyarkara is an Indonesian philosopher who has original way of thinking. This paper aims to explore and analyze his ideas of moral and decency. According to Driyarkara, moral is a human need. Without moral, humanity will be in chaos. Based on Driyarkara's point of view, moral is a consequence of consciousness; therefore, having high moral standard is a human nature. Furthermore, conscience can be a moral standard for determining right or wrong as long as the conscience itself has not been “raped”. When conducting a moral consideration, every human has to use his own reason which is reflected in Driyarkara's Purity of Reason Dialectic. For him, all moral efforts show that human always want to achieve the perfection which is considered as God. The Driyarkara ethics could be classified as the deontological ethics. But it is the deontological ethics which has theological, humanist-naturalist, and axiological dimensions so that it can be defined as teleological as well. If we correlate the Driyarkara ethics and the Postmodern Era where morality has already been blurring, we can place the Driyarkara ethics which is considered teleological and deontological as a solid alternative of morality.